Evaluation and Modification of Off-Host Flea Collection Techniques Used in Northwest Uganda: Laboratory and Field Studies - Borchert, Jeff N.; Eisen, Rebecca J.; Holmes, Jennifer L.; Atiku, Linda A.; Mpanga, Joseph T.; Brown, Heidi E.; Graham, Christine B.; Babi, Nackson; Montenieri, John A.; Enscore, Russell E.; Gage, Kenneth L. (Journal of medical entomology, 2012)
Quantifying the abundance of host-seeking ßeas is critical for assessing risk of human exposure to ßea-borne disease agents, including Yersinia pestis, the etiological agent of plague. Yet, reliable measures of the efÞcacy of existing host-seeking ßea collection methods are lacking. In this study, we compare the efÞcacy of passive and active methods for the collection of host-seeking ßeas in both the laboratory and human habitations in a plague-endemic region of northwest Uganda. In the laboratory, lighted “Kilonzo” ßea traps modiÞed with either blinking lights, the creation of shadows or the generation of carbon dioxide were less efÞcient at collecting Xenopsylla cheopis Rothchild and Ctenocephalides felis Bouche´ ßeas than an active collection method using white cotton socks or cotton ßannel. Passive collection using Kilonzo light traps in the laboratory collected signiÞcantly more X. cheopis than C. felis and active collection, using white socks and ßannel, collected signiÞcantly more C. felis than X. cheopis. In Þeld studies conducted in Uganda, Kilonzo traps using a ßashlight were similar in their collection efÞcacy to Kilonzo traps using kerosene lamps. However, in contrast to laboratory studies, Kilonzo ßea traps using ßashlights collected a greater number of ßeas than swabbing. Within human habitations in Uganda, Kilonzo traps were especially useful for collecting C. felis, the dominant species found in human habitations in this area.
Keywords: Flea trap; Ctenocephalides felis; Xenopsylla cheopis; ßea, plague; Fea; plague